Development of a roof-to-floor convergence index for longwall face using combined finite element modelling and statistical approach. (March 2020) - Islavath, Sreenivasa Rao; Deb, Debasis; Kumar, Hemant
Abstract: Immediate roof of a longwall panel in India is composed of mostly low quality coal and shale and as a result, several roof fall incidents have occurred in between canopy tip and the face causing delay in production. The mine has several longwall panels and it is expected that similar conditions may prevail in all the panels. Roof-to-floor convergence at the face, shield leg pressure and abutment load in chain pillar are monitored to evaluate the stability of longwall face in terms of displacement as well as stresses. In view of that, a study is conducted to understand the deformation behaviour of roof-to-floor convergence and development of pressure in hydraulic legs after the web cut considering different combinations of main roof thickness, its overhung length behind the shield, and material type and setting load. This paper describes a methodology for estimation of roof-to-floor convergence using 3D finite element models before and after web cut. A statistical procedure is also enumerated for development of a unique roof-to-floor convergence index combining input parameters. For this purpose, a total of 216 3D finite element models are analysed considering Drucker-Prager material nonlinearity and having two legged powered support of 2 × 1152 tonne capacity surrounded by coal, rock mass and goaf. This study also compares the roof-to-floor convergence measured in the field to those estimated using the proposed convergence index. Highlights: A 3D powered support is modelled along with coal seam, rock mass and goaf to analyse deformation, stresses and plasticity. Total of 216 FEM models are developed by varying thickness, length and material type of main roof and setting pressure. Bar elements are considered to simulate the setting of powered support at desired pressure level in numerical environment. A new Convergence Index is developed using statistical technique to forecast roof to floor convergence in longwall face.